Primary Prophylaxis Indication for Docetaxel Induced Febrile Neutropenia in Elderly Patients with Non-Small Cell Lung Cancer. (8th August 2020) - Matsui, Akira; Morise, Masahiro; Tanaka, Ichidai; Ozone, Sachiko; Matsuzawa, Reiko; Koyama, Junji; Hase, Tetsunari; Hashimoto, Naozumi; Sato, Mitsuo; Hasegawa, Yoshinori
Abstract: In advanced non-small cell lung cancer (NSCLC), the reported incidence of febrile neutropenia (FN) caused by docetaxel (DTX) is 10–20% in clinical trial data. However, FN incidence caused by DTX in real-world setting remains unclear. We evaluated FN incidence caused by DTX and identify risk factors of FN in real-world setting. One hundred and seventy-one NSCLC patients treated with DTX were retrospectively analyzed and 44 (26%) developed FN. Multivariate analysis identified higher age (≥65 years) and prior history of FN as independent risk factors for FN. Primary prophylaxis for FN might be recommended in elderly patients with/without prior history of FN.